The diagnostic value of Rosemont and Japanese diagnostic criteria for ‘indeterminate’, ‘suggestive’, ‘possible’ and ‘early’ chronic pancreatitis - Sheel, Andrea R. G.; Baron, Ryan D.; Sarantitis, Ioannis; Ramesh, Jayapal; Ghaneh, Paula; Raraty, Michael G. T.; Yip, Vincent; Sutton, Robert; Goulden, Michael R.; Campbell, Fiona; Farooq, Ammad; Healey, Priya; et al. (Pancreatology, 2018)
Background - Longitudinal data are lacking to support consensus criteria for diagnosing early chronic pancreatitis. - Methods - Retrospective single centre study of the initial evidence for chronic pancreatitis (CP), with reassessment after follow-up (January 2003-November 2016). - Results - 807 patients were previously diagnosed with chronic pancreatitis. This diagnosis was rejected in 118 patients: 52 had another pathology altogether, the remaining 66 patients formed the study population. 38 patients with ‘normal’ imaging were reclassified as chronic abdominal pain syndrome (CAPS), and 28 patients had minimal change features of CP on EUS (MCEUS) but never progressed. Strict application of the Japanese diagnostic criteria would diagnose only two patients with early CP and eleven as possible CP. Patients were more likely to have MCEUS if the EUS was performed within 12 months of an attack of acute pancreatitis. 40 patients with MCEUS were identified, including an additional 12 who progressed to definite CP after a median of 30 (18.75-36.5) months. Those continuing to consume excess alcohol and/or continued smoking were significantly more likely to progress. Those who progressed were more likely to develop pancreatic exocrine insufficiency, require pancreatic surgery and had higher mortality. - Conclusion - There needs to be more stringent application of the systems used for diagnosing chronic pancreatitis with revision of the current terminology ‘indeterminate’, ‘suggestive’, ‘possible’, and ‘early’ chronic pancreatitis. All patients with MCEUS features of CP require ongoing clinical follow up of at least 30 months and all patients with these features should be strongly counselled regarding smoking cessation and abstinence from alcohol.
Gesehen am 01.10.2019